PERSPEKTIF MAQÂ?ID SYARI’AH TERHADAP SISTEM SADOH BURUH TANI DALAM TRADISI NGERAMPEK DI DESA KURIPAN SELATAN KECAMATAN KURIPAN KABUPATEN LOMBOK BARAT - Fauzi, Muhammad (Al-Muqaronah: Jurnal Perbandingan Madzhab dan Hukum, 2022)
The form of muamalah transaction that is often carried out by the Sasak tribe community, especially the people of South Kuripan Village, Kuripan West Lombok is the tradition of the ngerampek sadoh (Wage) system, this tradition of the ngerampek sadoh (Wage) system has been going on for a long time, and has even become a tradition that has been passed down from generation to generation until now. This. The discussion in this research concerns the sadoh system of farm workers in the "ngerampek" tradition in Kuripan Selatan Village, Kuripan District, West Lombok, NTB and what is the Maqhasid Syari'ah Perspective on the sadoh system of farm workers in the ngerampek tradition in Kuripan Selatan Village, Kuripan District, West Lombok, NTB. Sadoh System (Wages) in the Ngerampek Tradition in Kuripan Selatan Village, Kuripan, West Lombok, the rental period for agricultural labor services in the ngerampek tradition does not have clear time provisions for mu'jir and musta'jir, only the rental period for services is until the end of the harvest (conditional), wages depending on the harvest, if the harvest is 9 quintals then the wages are 1 quintal, the wages depend on the harvest location, if the location is difficult then the wages are a lot, otherwise the wages are small, wages are based on a piece rate or batch system and depend on the harvest, and if viewed from the perspective of maqâ?id syari'ah then The wage system in this ngerampek tradition has legal consequences which are detailed as follows: the rental period for agricultural labor services and wages depending on the harvest that apply in this tradition are permitted because in the custom what is seen is that its existence is carried out for the sake of maintaining ?aruriyyatil khamsah and achieving benefit between both parties, while the wage system depends on the harvest and wages with a piece rate or bangketan system and depending on the harvest are prohibited in order to prevent conflict (sadd al-?ari'ah)